A Battery-Aware High-Throughput MAC Layer Protocol in Sensor Networks. (3rd October 2010) - Watfa, Mohamed K.; Selman, Samir; Denkilkian, Hovig
Abstract : Energy savings have always been the primary concern in wireless sensor network protocols, however there are applications where latency and throughput are prioritized over energy efficiency and are so significant that the application would not be able to satisfy its requirements without them. The communication unit and the antenna operation consume most of the battery-powered energy of the node. Thus, the access to the medium must be controlled in a very strict manner in order to avoid collisions which result in lost transmissions and have a dramatic impact on the lifetime of the network. Although existing duty cycle MAC protocols are power efficient, they introduce significant end-to-end delivery latency and provide poor throughput. In this paper, we propose SN-MAC, a CDMA-based power controlled medium access protocol that uses both transmitter-based and receiver-based CDMA inside a formed cluster, and uses a TDMA schedule to make the cluster heads communicate with the base station. Our algorithm targets latency and throughput needs in addition to its ability to increase the overall network lifetime. We provide a head-to-head comparison with other protocols through extensive simulations focusing on the performance in terms of latency, throughput, and energy consumption.